The Influence of Human Factor in Aircraft Maintenance - Darko Virovac; Anita Domitrović; Ernest Bazijanac (Promet - Traffic&Transportation, 2017)
Human factor is one of the safety barriers which is used in order to prevent accidents or incidents of aircraft. Therefore, the question is to which extent the error caused by human factor is included into the share of errors that are madeduring aircraft maintenance. In the EASA approved aircraft maintenance organisation, which includes in its working system the human factor as well, the tendency is to apply the approach by continuous monitoring and analysis of errors in aircraft maintenance. Such approach achieves advance prevention or reduction of the occurrence of harmful events, such as accidents, incidents, injuries and in a wider sense damages related to aircraft operation and maintenance. The research presented in this paper is a result of gathering and systematization of errors caused by human factors over the last five years in one organisation for aircraft maintenance certified according to the European standards. The study encompasses an analysis of 28 (twenty-eight) investigations of individual cases and provides insight into the main factors of errors. The results of analyses on the cause of occurrence of human error show similar results like the Boeing study which was carried out for the world fleet.